Pengaruh Web Trace and Tracking, Logistic Service Quality dan Penanganan Komplain Terhadap Kepuasan Konsumen (Studi Kasus Pada Layanan JNE Malang) - Arif Kurniawan Santoso; Rois Arifin; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis research aims to analyze the impact of network trace and tracking, logistics service quality, and complaint handling on customer satisfaction of the Malang branch of JNE service users. The method used in this study is multiple linear regression analysis. The samples used in this study refer to Ferdinand's purposeful sampling technique, that is, the researcher subjectively selects the purposeful sample, and there are 75 respondents in total. The results of this study also show the significant impact of Web tracking and tracking variables, logistics service quality, and JNE service user Malang branch on customer satisfaction complaint handling.Part of the test results show that Web tracking variables and tracking variables have a significant impact on the customer satisfaction of JNE service users Malang branch and complaint handling has a significant impact on the customer satisfaction of JNE service users Malang branch, while the variable service part of logistics quality does not Affect customer satisfaction JNE service user Malang branch. Keywords: Website Tracking and Tracking, Logistics Service Quality, Complaint Handling, Customer Satisfaction